Using Heartfulness Meditation and Brainwave Entrainment to Improve Teenage Mental Wellbeing - Yadav, Ghazal Suhani; Cidral-Filho, Francisco José; Iyer, Ranjani B. (Frontiers in Psychology, 2021)
Teenagers are highly susceptible to mental health issues and this problem has been exacerbated by the quarantine restrictions of COVID-19. This study evaluated the use of Heartfulness Meditation and Audio Brainwave Entrainment to help teenagers cope with mental health issues. It used 30-minute Heartfulness meditation and 15-minute brainwave entrainment sessions with binaural beats and isochronic tones 3 times a week for 4 weeks. Using a pretest-posttest methodology, participants were asked to complete a survey battery including the Pittsburgh Quality of Sleep Index, Perceived Stress Scale, Patient Health Question-9, Profile of Mood States, and Cambridge Brain Health assessment. Participants (n=40) were divided into 4 experimental groups: the control group (n=9), Audio Brainwave Entrainment group (n=9), Heartfulness Meditation group (n=10), and a combined group (n=12), for a 4-week intervention. Data were analyzed with paired t-tests. The singular Audio Brainwave Entrainment group did not see statistically significant improvements, nor did any of the intervention groups for brain health (p>0.05). This study, however, proved the efficacy of a 4-week Heartfulness Meditation program to regulate overall mood (p=.00132), stress levels (p=.0089), state depression (POMS; p=.0037), and anger (p=.002). Results also suggest adding Audio Brainwave Entrainment to Heartfulness Meditation may improve sleep quality (p=.0377) and stress levels (p=.00016).